The Morphological Process of Food Lexicon after COVID-19 - Widiatmika, Putu Wahyu; Segara, Ida Bagus Made Ari; Wulandari, Ni Komang Ayu (EDUCAFL: Journal on Education of English as Foreign Language, 2023)
The era of post-COVID-19 has shown a shift in lifestyle in terms of meal consumption among people around the world. It is depicted in the creation of healthy and plant-based foods. This study aimed to analyze the techniques of word formation about food and diet trends. The data of this study were new lexicons of food and diet trends taken from texts and scripts derived from different sources on the internet, such as news articles and blogs. The data were collected through the documentation method with a note-taking technique. Yule’s theory of word formation was applied to analyze the data with a qualitative method. The result showed that linguistics, particularly morphology, could contribute to the current living trends in the making of new terms. The terms found were food and diet lexicons created with various techniques, such as compounding, blending, borrowing, clipping, and acronyms.